Long-Term Wu Qin Xi Exercise on Response Inhibition and Cortical Connectivity in Parkinson's Disease: Design and Implementation of a Randomized Controlled Clinical Trial - Wang, Zhen; Zhang, Lan-Lan; Wu, Yin; Zhang, Jian; Liu, Ke (Frontiers in Neurology, 2021)
Background: Motor symptom disorders in patients with Parkinson disease (PD) are closely related to reduced inhibitory ability. Although exercise has been shown to improve this ability in patients with PD, its effects on proactive and reactive inhibition have not been determined. Most previous studies of inhibitory control disorder in people with PD have been behavioral, and little attention has been paid to functional cortical connectivity. Wu Qin Xi, a low–medium-intensity qigong exercise that is safe and easy to do for elderly individuals, can support physical well-being and help prevent and alleviate disease. In this study, our aims were to explore the effects of a long-term Wu Qin Xi intervention on response inhibition and to examine how improved inhibition control relates to cortical connectivity using dual-site paired-pulse transcranial magnetic stimulation (ppTMS), in patients with mild–moderate PD. Methods: A single-blind randomized controlled trial will be conducted. A total of 90 elderly subjects will be recruited and allocated randomly to Wu Qin Xi, balance exercise, and healthy control groups. The exercise interventions will be implemented in three 90-min sessions per week for 24 weeks; the healthy control group will receive no intervention. The primary assessments will be response inhibition metrics and task-based ppTMS. The secondary outcomes will include motor symptom severity, mobility, balance, emotional state, and quality of life. Assessments will be conducted at baseline, at the conclusion of the intervention period (week 24), and a few months after the intervention (week 36 follow-up). Discussion: This study is designed to provide insights into the effects of practicing Wu Qin Xi on response inhibition function in people with PD. The results will provide evidence on the value of traditional Chinese exercise as a therapeutic rehabilitation option for these patients. They will also provide data addressing how brain function–related cortical connectivity is related to reactive versus proactive inhibition in people with PD participating in an exercise intervention. Trial registration number: This study has been registered prospectively in the Chinese Clinical Trial Registry (ChiCTR2000038517, 18 January 2021).